Simba Kuat: Implementation of an Environmental Cadre Program from School to Village Level in Keluang Village, Tunkal Ilir, South Sumatra - Aprillia, Eka; Hendrawan, Wawan; Abistya, Risang Raditya (International Journal of Social Science and Community Service, 2024)
Since its inception in 2021 at SMP Negeri 2 Tungkal Ilir, the Synergy Towards a Healthy and Civilized School (Simba Sehati) program has successfully produced environmental cadres through the concept of an environmentally friendly school. Students have become familiar with and skilled in applying Clean and Healthy Living Behavior (PHBS), environmental conservation efforts, and organic farming. The skills acquired include waste bank management, maggot cultivation from organic waste, wastewater treatment, biopore hole creation, hydroponic cultivation of Family Medicinal Plants (TOGA), fish farming in buckets ("budidamber"), and public health. This year, the Simba Sehati program is being implemented at the village level under the Synergy of Ramba Field Towards a Clean and Healthy Keluang (Simba Kuat) program, with the village community as the beneficiaries. In its development, the Simba Kuat program involves environmental cadres actively transferring knowledge to community groups. The program aims to improve the health and environmental quality of Keluang Village and create opportunities for additional income for the residents.